Developments in commuting in the municipalities of Lower Saxony between 1987 and 1998: Housing and work move further apart - Schaffner, Joey (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
This article reports on a study of changes in commuting patterns in Lower Saxony between 1987 and 1998. During this period the average commute increased in distance by 10 % to 10.7 km. Regional differences between agglomeration and rural areas have largely disappeared. The average amount of time taken to travel between home and work has remained almost constant for 25 years at slightly over half an hour; in other words, commuters have managed to avoid spending more time travelling to and from work. This has been achieved by an unmistakable increase in private-car use, which is reflected in a rise in motorised private traffic levels of some 25 %.
Keywords: Article